Glucocorticoid insensitivity by staphylococcal enterotoxin B in keratinocytes of allergic dermatitis is associated with impaired nuclear translocation of the Glucocorticoid Receptor α. Issue 3 (December 2018) - Huang, Ke; Ran, Lei; Wang, Wei; Zhou, Rong; Cai, Xiaowei; Li, Ran; Li, Yuanchao; Zhou, Chunli; He, Wei; Wang, Rupeng
Highlights: SEB induces insensitivity to glucocorticoids in atopic dermatitis. SEB inhibits dexamethasone-induced GRα nuclear translocation in keratinocytes. Accumulation of cytoplasmic GRα is related to elevation of FKBP51 in HaCaT cells. Abstract: Background: staphylococcal enterotoxin plays an important role in patients with glucocorticoid (GC)-resistant atopic dermatitis (AD), but the exact mechanism is not fully understood. Objective: The aim of this study was to investigate the mechanisms underlying the ability of staphylococcal enterotoxin B (SEB) to induce steroid insensitivity through impaired nuclear translocation of GRα in keratinocytes. Methods: The steroid-resistant AD induced by SEB was assessed by analyzing dermatitis score, dermal thickness, scratching behavior, infiltrating cells/HPF, levels of SEB-specific IgE and IgG2a antibody. In addition, dexamethasone (DEX)-induced GRα nuclear translocation and keratinocyte-derived cytokines and chemokines were analyzed in the lesional keratinocytes of AD and in HaCaT cells. Furthermore, the expressions of immunophilins FKBP51, FKBP52 and HSP90 responsive to GC in HaCaT cells were determined in the presence of SEB. Results: SEB dose-dependently diminished the inhibitory effect of DEX on dermatitis score, dermal thickness, scratching behavior, infiltrating cells/HPF, keratinocyte-derived cytokines and chemokines such as RANTES, MCP-1, TSLP and GM-CSF. In vivo and in vitro data showed that in the presence of DEX, SEB dose-dependently caused a marked decrease of GRα nuclear translocation in lesional keratinocytes of AD and in HaCaT cells. Importantly, in the presence of DEX, SEB increased the expression of FKBP51 and the product of keratinocyte-derived cytokines and chemokines in HaCaT cells. Conclusion: These results demonstrate that GC insensitivity by SEB in keratinocytes of AD is associated with impaired nuclear translocation of the GRα. Increased DEX-induced FKBP51 by SEB may contribute to accumulation of the GRα in cytoplasm of keratinocytes.